National Policy for Rare Diseases, 2021 – A critical perspective - Dubey, Manju; Kumar, Mohan (Indian Journal of Community Health, 2022)
More than 8% of the global population is affected by a rare disease and >50% affected are children (30% of whom will die before 5 years). There are 6,000-8,000 classified rare diseases – 80% are genetically based – with less than 500 FDA approved treatments (or <5% have therapies) available to treat them. Lack of standard definition and community-based epidemiological data in India limits the estimation of prevalence and/or disease burden; though extrapolations at 6% to 8% show 72 to 96 million affected individuals. The Government of India approved the “National Policy for Rare Diseases, 2021” on 30th March 2021. It is a step in the right direction; at the time it necessitates optimal utilization of allocated resources and timely appraisal of the policy itself.